Les Mystères : nouvelles perspectives - Philonenko, Marc; Lehmann, Yves; Pernot, Laurent (Brepols, 2017)
This multidisciplinary volume features a comparative and critical study of the mysteries in the major religions of the Antiquity. It considers ceremonies, rituals, sacraments and the theological content, made up of doctrine and dogma. The domains taken into consideration include Greek and Roman paganism, Judaism and Christianity, Mazdeism, Eastern cults, as well as their prolongations until the Middle Ages and the Reformation. This study has as a starting point the vocabulary and the linguistic transpositions and exchanges, in order to move on to the wider field of the major religious and philosophical issues. Profound unity of the theme in this volume is due to the theme’s paradoxically great nature. Any mystery is intended to be revealed. It kindles great expectations and appears concealed only to be better disclosed. This promising dialectic construction explains the crucial role played by mysteries in the history of religions.